2017
DOI: 10.1142/s0218216517500596
|View full text |Cite
|
Sign up to set email alerts
|

Right-angled Artin groups and full subgraphs of graphs

Abstract: For a finite graph Γ, let G(Γ) be the right-angled Artin group defined by the complement graph of Γ. We show that, for any linear forest Λ and any finite graph Γ, G(Λ) can be embedded into G(Γ) if and only if Λ can be realised as a full subgraph of Γ. We also prove that if we drop the assumption that Λ is a linear forest, then the above assertion does not hold, namely, for any finite graph Λ, which is not a linear forest, there exists a finite graph Γ such that G(Λ) can be embedded into G(Γ), though Λ cannot b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…However, E. Lee and S. Lee [5] pointed out that the above "Theorem" is incorrect by giving a counter-example. Thus the author's proof of Theorem 1.1 in [3] is not valid.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, E. Lee and S. Lee [5] pointed out that the above "Theorem" is incorrect by giving a counter-example. Thus the author's proof of Theorem 1.1 in [3] is not valid.…”
Section: Introductionmentioning
confidence: 99%
“…The complement Λ c of a graph Λ is the graph consisting of the vertex set V (Λ c ) = V (Λ) and the edge set E(Λ c ) = {{u, v} | u, v ∈ V (Λ), {u, v} / ∈ E(Λ)}. In [3] the author "proved" the following theorem. Theorem 1.1.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kim and Koberda showed that the family of finite trees provides a universal family of graphs for right-angled Artin groups. Using the fact that if Γ 1 is an edge-contraction of Γ 2 then G(Γ 1 ) G(Γ 2 ) [Kim08, KK13], we can see that the family of finite trees with degree 3 at each vertex is also universal [Kat16]. It would be interesting to find a universal family smaller than this.…”
Section: Introductionmentioning
confidence: 99%